A HEMT large‐signal model for use in the design of microwave switching circuits. Issue 3 (11th December 2019) - Tao, Yuan; Hu, Zhi Fu; Fan, Yong
Abstract: The nonlinear sources of switch‐HEMTs have been well analyzed by using the measured data. The small signal intrinsic capacitances (under both positive and negative V ds operation) have been extracted by an extended small signal model. one‐dimension capacitance model has been effectively applied to model the small signal incremental capacitances directly extracted from the key operation region, which has also automatically taken into account the surface trapping effects. A new capacitance model has been effectively proposed to well fit the key nonlinear source (the deep subthreshold capacitance) of switch‐HEMTs. Simple switching function and additional voltage dependence have been applied to model the wide linear‐region (from high‐ V gs region to deep subthreshold region) of channel current. On/off state small signal insertion loss, small signal isolation, weak harmonics, and power carrying capabilities are accurately predicted by the large signal model. The model shows very good convergence of circuit simulation. Meanwhile, the simple equations and distinguishing among the capacitances accurately make the scaling rules simple and accurate.